Respuesta :

Answer:The remainder can be calculated by doing the following steps;

Step-by-step explanation:

Ver imagen iqbalamna367

The remainder when f(x) = x⁴ - 5x³ + 3x² - 2x +7 is divided by x - 1 is 4.

Polynomial is an expression that involves only the operations of addition, subtraction, multiplication of variables.

The remainder theorem states that when a polynomial, f(x), is divided by a linear polynomial , x - a, the remainder of that division will be equivalent to f(a).

Given that f(x) = x⁴ - 5x³ + 3x² - 2x +7 is divided by x - 1

x - 1 = 0

x = 1

f(1) = 1⁴ - 5(1)³ + 3(1)² - 2(1) + 7 = 4

The remainder when f(x) = x⁴ - 5x³ + 3x² - 2x +7 is divided by x - 1 is 4.

Find out more on polynomial at: https://brainly.com/question/2833285

ACCESS MORE